Controversies - Erasmus, Desiderius, -1536 (Erasmus, Desiderius, -1536. Works. 1974, 1998)
In these four responses to his critics, Erasmus discusses popular concerns such as the relations between the sexes, celibacy, marriage, divorce, and how to live a good life.